Metabolism in myocardial ischaemia and reperfusion with specific reference to the role of glucose - King, Linda Mary (MRC/UCT Cape Heart Centre, 2017)
Hypothesis: Glucose is known to be protective in moderate low flow ischaemia due to the production of glycolytic ATP. However, it is questioned whether glucose would still be protective in ultra-low flow ischaemia. Firstly, glycolysis is thought to be inhibited, and secondly, deleterious glycolytic metabolites accumulate. Our hypothesis was that in ultra-low flow ischaemia, glucose utilisation is not inhibited at the level of glycolysis, but by delivery. Increased delivery of glucose should result in increased production of protective glycolytic ATP, but the rate of metabolite accumulation would also increase. Using ultra low flow rates, I wished to investigate how to achieve optimal rates of glycolysis, and how such rates would be balanced by any detrimental component of metabolite accumulation. Methods: The isolated Langendorff-perfused rat heart, with a left ventricular balloon to record ischaemic contracture and reperfusion stunning, was used, with severe flow restriction. Glucose concentrations were changed and pre-ischaemic glycogen contents were altered by perfusion with different substrates (acetate - depletion~ glucose + insulin - loading) or by preconditioning, with 5 min ischaemia and 5 min reperfusion prior to sustained ischaemia. Results: Analysis of glucose uptake relative to delivery showed that in severe low flow ischaemia, the extraction of glucose was increased, and glycolysis was thus limited more by substrate supply than by enzyme inhibition. Analysis of metabolites confirmed this concept. The optimal glucose concentration during severe low flow ischaemia was 11 mM, giving maximal recovery on reperfusion. Both lower and higher glucose concentrations increased ischaemic contracture. Changes in pre-ischaemic glycogen levels correlated with the time to onset of contracture, such that a reduction in glycogen accelerated contracture. Prior glycogen depletion or loading did not improve functional recovery. The benefits of preconditioning on reperfusion function following sustained total global ischaemia could not be related to glycogen depletion. If preconditioning were followed by sustained low flow ischaemia, glucose uptake was increased, but no benefit was found, possibly because a low residual flow abolished the effects of preconditioning. Many of the above results are consistent with the hypothesis that too low a rate of glycolysis results. in insufficient ATP production for protection, while excess glycolytic rates lead to excess metabolite accumulation with detrimental effects. Conclusions: Provision of glucose at the correct concentration, when the benefit associated with glycolytic ATP outweighs the detriment associated with moderate metabolite accumulation, is protective to the low-flow ischaemic myocardium, which can upregulate its ability to extract glucose. Improved residual flow enhances this benefit. Prior glycogen depletion is not beneficial, despite a reduced metabolite accumulation. This mechanism cannot be related to the protective effect of preconditioning.